Candida rugosa Lipase: A Traditional and Complex Biocatalyst - Dominguez de Maria, P.; Alcantara, A. R.; Carballeira, J. D.; de la Casa, R. M.; Garcia-Burgos, C. A.; Hernaiz, M. J.; Sanchez-Montero, J. M.; Sinisterra, J. V. (Current Organic Chemistry, 2006)
Different commercial preparations from Candida rugosa lipase lead often to an irreproducible behaviour when employed in slightly hydrated media, even when different samples from the same supplier are used. This conduct is triggered by several causes, such as the different concentration of the
Keywords: Transesterification